Molecular analysis of regulation of gene expression of the human erythroid anion exchanger (AE) 1 - König, Jörg; et al. (Febs Letters, 1998)
The anion exchange protein AE1 is the most abundant membrane protein in human erythrocytes mediating the electroneutral chloride/bicarbonate exchange. We identified a promoter region in the 5' flanking region of the human AE1 gene which controls transcription in a cell type independent manner. In addition a second, distal promoter element mediates gene expression only in erythroid cells and in dependence upon differentiation. Within this distal promoter region we defined a 44 bp sequence containing a novel CT-rich motif with very strong promoter activity whereas a second 28 bp segment suppresses gene expression. Copyright (C) 1998 Federation of European Biochemical Societies.
Created from Fastlane, Scopus look-up
Keywords: Anion exchanger 1; Band 3; CT-rich region; Erythroid specific expression; Red blood cell maturation